1998
DOI: 10.1021/ma980396n
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Ring-Opening Polymerization and Copolymerization of 8-Octanolide by Lipase Catalyst

Abstract: Enzymatic ring-opening polymerization and copolymerization of a nine-membered lactone, 8-octanolide (8-OL), was performed in isooctane by using various lipases of different origin as catalyst. The polymerization behavior greatly depended on the lipase origin. Candida antarctica and Pseudomonas cepacia lipases (lipases CA and PC, respectively) showed high catalytic activity toward the present polymerization. Pseudomonas fluorescens lipase (lipase PF) also catalyzed the polymerization of 8-OL. The polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 31 publications
2
93
0
Order By: Relevance
“…[48,52] In contrast to lipase PF, Lipase CA exhibited higher catalytic activity for e-CL than for macrolides. The ROP of e-CL (1 mmol) with 10 mg of lipase CA in bulk at 60 8C for 4 h gave poly(e-CL) of M n 5 200 at 72% yields.…”
Section: Terminator Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48,52] In contrast to lipase PF, Lipase CA exhibited higher catalytic activity for e-CL than for macrolides. The ROP of e-CL (1 mmol) with 10 mg of lipase CA in bulk at 60 8C for 4 h gave poly(e-CL) of M n 5 200 at 72% yields.…”
Section: Terminator Methodsmentioning
confidence: 99%
“…[52] Some enzyme screening data for ROP of PDL are also given in Table 1. Ring-opening copolymerization of PDL with four monomers, d-VL, e-CL, UDL, and DDL, by lipase PF and lipase PC at 60 8C in bulk was carried out to give copolymers with M n ranging from 1 200 to 6 300, not being statistically random (Scheme 4).…”
Section: Finding Of Lipase Catalyst and The Scope Of Reactionsmentioning
confidence: 99%
“…When 2,2-dibutyl-2-stanna-1,3-dioxepane was used as catalyst, the copolymerization of TMC with b-butyrolactone produced A-B-A triblock copolymer, whereas the random copolymer was formed from d-valerolactone or e-CL 20) . We have already reported that the ring-opening copolymerization of lactones proceeded via the lipase catalysis 21,22) . Here, the copolymerization of cyclic dicarbonates with lactones using lipase CA as catalyst has been examined (Scheme 2).…”
Section: Enzymatic Copolymerization Of Cyclic Dicarbonates With Lactonesmentioning
confidence: 99%
“…Lots of investigations on different ring size of lactones, solvent effect, and an enzymatic activity of lipases immobilized on different matrix have been carried out. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In case of condensation of diol and diacid with aliphatic chain, the high molecular weight polyester can be obtained by removing a leaving group. Klibanov et al have explored the enzymatic catalyzed asymmetric polymerization of aliphatic diol and diacid.…”
Section: Introductionmentioning
confidence: 99%